2021
DOI: 10.23937/2643-3885/1710054
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Management of K-Wires in Percutaneous Foot Surgery

Abstract: Introduction: When a Kirschner wire (K-wire) is used percutaneously, the protruding end often causes discomfort and is associated with an increased risk of complications, such as pin loosening, infection, injury, etc. This study was undertaken to determine the ideal postoperative management when using these implants. We describe a surgical alternative for K-wire management in foot surgery. Materials and method:A prospective, descriptive study was conducted. A total of 39 patients (70 procedures) were enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…7,8 Studies show that K-wire fixation in hand and foot surgery yielded complication rates of 14% and 2.85%, respectively. 7,8 Nevertheless, recent studies have demonstrated the utility of plates for their robust allograft fixation for CLO. 4,5 Plate technology used for fracture fixation provides increased allograft stability but potential complications include hardware failure, loosening, plate discomfort, deep tissue infection, greater biological insult due to soft tissue dissection and bone stripping, and nonunion.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…7,8 Studies show that K-wire fixation in hand and foot surgery yielded complication rates of 14% and 2.85%, respectively. 7,8 Nevertheless, recent studies have demonstrated the utility of plates for their robust allograft fixation for CLO. 4,5 Plate technology used for fracture fixation provides increased allograft stability but potential complications include hardware failure, loosening, plate discomfort, deep tissue infection, greater biological insult due to soft tissue dissection and bone stripping, and nonunion.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study comparing outcomes of K-wire fixation and plates for patients receiving CLO in painful pediatric FF. Advantages of using K-wires include lower costs and ease of insertion, whereas disadvantages include higher rates of superficial wound infections, pin site irritation, pin migration, potential loss of reduction, and in rare instances, deep tissue infections and osteomyelitis 7,8 . Studies show that K-wire fixation in hand and foot surgery yielded complication rates of 14% and 2.85%, respectively 7,8 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations